Real-time sign language framework based on wearable device: analysis of MSL, DataGlove, and gesture recognition - Alamoodi, Abdullah Hussein (Tanjung Malim, 2021)
Real-time sign language framework based on wearable device: analysis of MSL, DataGlove, and gesture recognition by Alamoodi, Abdullah Hussein